1981
DOI: 10.1017/s0376892900028125
|View full text |Cite
|
Sign up to set email alerts
|

Run-off and Infiltration Losses Related to Shifting Agriculture (Jhum) in Northeastern India

Abstract: 1 6 ' i. TABLE IV. Total Loss of Nutrients (kg/ha/yr) in Run-off Water from Agro-ecosystems under Various Jhum Cycles.M J J A S 0 M J J A S 0 MONTHS M J J A S 0 Fig. 5. Changes in concentration of potassium (A), calcium (B), and magnesium (C), in run-off water during the monsoon at time of cropping after bum on sites under 30-(•), 10-(o), and 5-(*•/, years'Jhum cycles. J J A S 0 M J J A S 0 MONTHS M J J A S 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Overland flow and soil loss from the wasteland was low compared to agricultural land as it was not disturbed and was covered by ground vegetation. Toky and Ramakrishnan (1981) also made similar observations on fallow lands in a shifting agriculture system in northeast India. In spite of more overland flow from the large cardamom based agroforestry system in the present study, soil loss was low because of good canopy coverage and complete ground cover by perennial cardamom bushes.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Overland flow and soil loss from the wasteland was low compared to agricultural land as it was not disturbed and was covered by ground vegetation. Toky and Ramakrishnan (1981) also made similar observations on fallow lands in a shifting agriculture system in northeast India. In spite of more overland flow from the large cardamom based agroforestry system in the present study, soil loss was low because of good canopy coverage and complete ground cover by perennial cardamom bushes.…”
Section: Discussionsupporting
confidence: 60%
“…Soil loss from the watershed was high (794 Mg/km 2 /yr), however within the range of 500-1000 Mg/km 2 /yr for the Himalaya reported by Milliman and Meade (1983). Soil losses as high as 3005 Mg/km 2 /yr, were recorded in an agro-ecosystem under 5 years of shifting cultivation (Toky and Ramakrishnan, 1981). Therefore, land-use practices such as agroforestry (280 Mg/ km 2 /yr) and stabilized cultivation (1298 Mg/ km 2 /yr) in the present study, were found better in terms of reducing soil losses compared to shifting cultivation.…”
Section: Discussionsupporting
confidence: 49%
“…Lal, 1989Lal, , 1996, and shifting cultivation in Asia (e.g. Toky and Ramakrishnan, 1981). Giertz and Diekkruger (2003) and Giertz et al (2005) compared agricultural areas with natural vegetation in Benin (West Africa), but the time since conversion was unknown.…”
Section: G Nyberg Et Al: Soil Property Changes In a 120 Yr Forestmentioning
confidence: 99%
“…Shifting cultivation, also known as "Slash and Burn" or "Swidden agriculture" and as "Jhum cultivation" in north-east India, where it is a predominant activity for the majority of the population, is often described as an inefficient, destructive practice, which contributes to deforestation and lowland sedimentation (Sillitoe, 1998). Reducing the jhum cycle during recent years has put pressure on resources and thus the productivity of land degradation, increased levels of soil erosion, hydrological imbalances and forest degradation all of which have caused reductions in yields and insecurity of food sources (Toky & Ramakrishnan, 1981). Understanding the characteristics of hydrological processes and regime change is important for driving the solutions to rational use of the lake water and limiting the environmental degradation in the region.…”
mentioning
confidence: 99%